CD4 T cell-intrinsic STING signaling controls the differentiation and effector functions of TH1 and TH9 cells. Issue 1 (28th January 2022) - Benoit-Lizon, Isis; Jacquin, Elise; Rivera Vargas, Thaiz; Richard, Corentin; Roussey, Aurélie; Dal Zuffo, Ludivine; Martin, Tiffany; Melis, Andréa; Vinokurova, Daria; Shahoei, Sayyed Hamed; Baeza Garcia, Alvaro; Pignol, Cassandre; et al.
Abstract : Background: While stimulator of interferon genes (STING) activation in innate immune cells of the tumor microenvironment can result in CD8 T cell-dependent antitumor immunity, whether STING signaling affects CD4 T-cell responses remains elusive. Methods: Here, we tested whether STING activation modulated the effector functions of CD4 T cells in vivo by analyzing tumor-infiltrating CD4 T cells and evaluating the contribution of the CD4 T cell-derived cytokines in the antitumor activity of the STING ligand 2′3′-cyclic guanosine monophosphate-adenosine monophosphate (cGAMP) in two mouse tumor models. We performed ex vivo experiments to assess the impact of STING activation on CD4 T-cell differentiation and investigate the underlying molecular mechanisms. Finally, we tested whether STING activation enhances TH 9 cell antitumor activity against mouse melanoma upon adoptive transfer. Results: We found that activation of STING signaling cell-intrinsically enhances the differentiation and antitumor functions of TH 1 and TH 9 cells by increasing their respective production of interferon gamma (IFN-γ) and interleukin-9. IRF3 and type I interferon receptors (IFNARs) are required for the STING-driven enhancement of TH 1 cell differentiation. However, STING activation favors TH 9 cell differentiation independently of the IFNARs/IRF3 pathway but through mammalian target of rapamycin (mTOR) signaling, underscoring that STING activation differentially affects the fate of distinct CD4 T-cell subsets. The therapeutic effect of STING activation relies on TH 1 and TH 9-derived cytokines, and STING activation enhances the antitumor activity of TH 9 cells upon adoptive transfer. Conclusion: Our results reveal the STING signaling pathway as a therapeutic target to boost CD4 T-cell effector functions and antitumor immunity.